Dynamical back‐action effects in low loss optomechanical oscillators. Issue 1 (8th August 2014) - Pontin, Antonio; Bonaldi, Michele; Borrielli, Antonio; Marino, Francesco; Marconi, Lorenzo; Bagolini, Alvise; Pandraud, Gregory; Serra, Enrico; Prodi, Giovanni A.; Marin, Francesco; Harris, Jack; Rabl, Peter; et al.
<x xml:space="preserve">Abstract</x> The problem of the stability of a cavity optomechanical system based on an oscillator having at the same time low optical and mechanical losses is addressed. As it is the aim to extend the use of optical squeezing as a tool for improving quantum limited displacement sensing at low frequency, a family of opto‐mechanical devices designed to work at frequencies of about 100 kHz was developed . The devices actually meet the initial design goals, but new requirements have emerged from the analysis of their behavior in optical cavities, due to the interaction between the cavity locking system and the low order normal modes of the devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>